2004
DOI: 10.1094/phyto.2004.94.7.730
|View full text |Cite
|
Sign up to set email alerts
|

RNA Silencing of the Introduced Coat Protein Gene of Turnip mosaic virus Confers Broad-Spectrum Resistance in Transgenic Arabidopsis

Abstract: The coat protein (CP) gene derived from Turnip mosaic virus (TuMV) isolate JO was introduced into Arabidopsis thaliana and the resulting transgenic progenies were analyzed for resistance to TuMV. Transgenic Arabidopsis plants with no detectable transcripts of the introduced CP gene exhibited complete resistance to TuMV. There was no significant correlation between the resistance and the copy number of the transgene. Instead, small interfering RNAs (siRNAs) were detected in these resistant plants, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
14
1
1
Order By: Relevance
“…Indeed, transgenic plants were shown to contain transgene-specific siRNAs. In contrast to experiments with RNA viruses (18,33,42,46) completely immune lines were not observed. Most transgenic lines, however, did show significant delays in symptom development, and two lines displayed highly resistant and even immune plants.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Indeed, transgenic plants were shown to contain transgene-specific siRNAs. In contrast to experiments with RNA viruses (18,33,42,46) completely immune lines were not observed. Most transgenic lines, however, did show significant delays in symptom development, and two lines displayed highly resistant and even immune plants.…”
Section: Discussioncontrasting
confidence: 74%
“…Noris et al (47) reported similar results for Tomato yellow leaf curl Sardinia virus, where this virus was able to infect tomato plants expressing siRNAs specific to AC1. Both cases contrast with RNA silencing-mediated resistance to RNA viruses, where the presence of virus-specific siRNAs in transgenic plants strongly correlates with virus resistance (18,33,42,46), indicating that RNA viruses are more susceptible to RNA silencing, possibly because both mRNAs and genomic RNAs can be the target of the silencing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis plants were also inoculated mechanically with an extract of PlAMV-GFP-infected N. benthamiana plants, which was prepared by grinding infected leaf tissues in 0.1 M phosphate buffer, pH 7.0, as described previously . N. benthamiana plants were also inoculated with AV3 (Hashimoto et al, 2008), CMV (Suzuki et al, 1991), PVX (Komatsu et al, 2010), PVY (Hidaka et al, 1992), RaMV (Komatsu et al, 2007), TMV , TRV (Ratcliff et al, 2001), TuMV (Nomura et al, 2004), or WClMV (Nakabayashi et al, 2002) mechanically. These viruses were detected by RT-PCR with total RNA isolated from the upper leaves of virus-inoculated plants at 20 DAI using the primers indicated in Supplemental Table 4 online.…”
Section: Virus Inoculation and Agroinfiltrationmentioning
confidence: 99%
“…Previously, we reported that transgenic Arabidopsis thaliana carrying the full coding region of a Turnip mosaic virus (TuMV)-CP gene showed complete resistance to TuMV isolates (Nomura et al 2004). The purpose of the present study was to determine the RNA silencing suppression ability of a mild strain of CMV isolated from tomato using TuMV-resistant transgenic A. thaliana plants (TuR-At) carrying posttranscriptionally silenced TuMV-CP transgenes.…”
Section: Introductionmentioning
confidence: 94%
“…Three TuR-At Arabidopsis lines, CP112-R1, CP202-R1, and CP232-R1, carrying TuMV-CP transgenes with posttranscriptionally silenced expression, and a TuMV strain, TuMV-JO, were described previously (Nomura et al 2004). Nontransgenic wild-type Col-0 of Arabidopsis thaliana was used as the control in these experiments.…”
Section: Arabidopsis Lines and Viral Strainsmentioning
confidence: 99%